2006
DOI: 10.1038/sj.ki.5001958
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of end-stage renal disease in India: A population-based study

Abstract: Chronic kidney disease (CKD) and end-stage renal disease (ESRD) are emerging public health problems in developing countries, and need changes in health-care policy. ESRD incidence data are not available from large parts of the developing world including South Asia. We report the ESRD incidence in a large urban population in India. ESRD incidence was estimated for four consecutive calendar years (2002-2005) among 572 029 subjects residing in 36 of the 56 wards of the city of Bhopal. These subjects are beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
192
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(209 citation statements)
references
References 11 publications
7
192
2
Order By: Relevance
“…Lean Diabetics were those diabetics who had other features of diabetes but were of BMI of around 18, and could maintain their sugars on OHAs as other T2DM individuals, Pancreatic Diabetes and GDM as an entity was made but the enrollment of the patient in the study was not done. Microalbuminuria prevalence in our study was found in around 9 percent of individuals which is at par with other reported studies, although the prevalence of known CKD a variable which was defined in our studies as individuals already a proven case and under nephrology treatment, and hence a lower prevalence of around 2.5 percent can be understood in our study, with eGFR studies at par prevalence would have been seen (68)(69)(70)(71) . Microalbuminuria was found to be statistically significantly associated with hypertension, P value <0.036, duration of diabetes and level of sugar control were not found to be statistically significant in our study.…”
Section: Not Known Hypothyroid Hperthyroidcontrasting
confidence: 41%
“…Lean Diabetics were those diabetics who had other features of diabetes but were of BMI of around 18, and could maintain their sugars on OHAs as other T2DM individuals, Pancreatic Diabetes and GDM as an entity was made but the enrollment of the patient in the study was not done. Microalbuminuria prevalence in our study was found in around 9 percent of individuals which is at par with other reported studies, although the prevalence of known CKD a variable which was defined in our studies as individuals already a proven case and under nephrology treatment, and hence a lower prevalence of around 2.5 percent can be understood in our study, with eGFR studies at par prevalence would have been seen (68)(69)(70)(71) . Microalbuminuria was found to be statistically significantly associated with hypertension, P value <0.036, duration of diabetes and level of sugar control were not found to be statistically significant in our study.…”
Section: Not Known Hypothyroid Hperthyroidcontrasting
confidence: 41%
“…Patients with declining eGFR are prone to DFI. In a developing country, the burden of CKD is higher [8] and it is further escalated due to DFI. If DFI occurs in patients with CKD stage 3 and stage 4, it may worsen the GFR decline and lead to ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Indians are at heightened risk for nephropathy, more than any other ethnic groups and declining of GFR was also faster. T2DM patients in India are at high risk of developing Chronic Kidney disease (CKD) and diabetes is now the leading cause of end stage renal disease (ESRD) in many regions of India [8]. The burden of CKD among the DM remains to be a global threat, as the treatment is expensive and lifelong.…”
Section: Introductionmentioning
confidence: 99%
“…India (V. Jha) CKD, diabetes and hypertension have been identified as increasing in prevalence in several small surveys. Diabetes is the commonest cause of end-stage renal diseases (ESRD); 73% of ESRD patients present less than 3 months before diagnosis [12].…”
Section: China (W Chen)mentioning
confidence: 99%